2015
DOI: 10.1167/iovs.15-16809
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Embryonic and Young Human Vitreous

Abstract: PURPOSE. The proteomic profile of vitreous from second-trimester human embryos and young adults was characterized using mass spectrometry and analyzed for changes in protein levels that may relate to structural changes occurring during this time. This vitreous proteome was compared to previous reports to confirm proteins already identified and reveal novel ones. METHODS.Vitreous from 17 human embryos aged 14 to 20 weeks gestation (WG) and from a 12-, a 14-, a 15-, and a 28-year-old was individually analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“… h Reported on gold and silica nanoparticles by Jo. 30 I Not previously reported in human vitreous by Semba, 26 Aretz, 27 Yee, 28 and Skeie. 29 …”
Section: Resultsmentioning
confidence: 92%
“… h Reported on gold and silica nanoparticles by Jo. 30 I Not previously reported in human vitreous by Semba, 26 Aretz, 27 Yee, 28 and Skeie. 29 …”
Section: Resultsmentioning
confidence: 92%
“…Recent proteomic analyses of human vitreous humor 48 50 have identified many hundreds of protein components, of which a core set of 231 proteins were detected in all studies. In the present study, after filtering against the matrisome database, we identified 200 components of the bovine vitreous.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, because of the large number of the new proteins identified in the rabbit vitreous that were not previously reported in human or rodent vitreous, it is possible that the rabbit may have a different protein profile compared to humans and rodents, therefore, caution should be taken in interpreting data from different species. It is also possible that sample preparation techniques used in this and other studies were different and may have resulted in the protein differences seen between our study and those previously published[ 18 21 ]. Additional comparative protein profiling of the rabbit vitreous and the vitreous protein profile of human and mouse using the same sample preparation and analysis methods might be wanted.…”
Section: Discussionmentioning
confidence: 59%
“…Other studies such as those performed by Aretz et al[ 19 ] and Murphy et al[ 20 ] identified 1111 and 1205 proteins from human vitreous respectively, the latter included proteins identified with 1 unique peptide. Recently Yee et al detected 1217 proteins in fetal and young adult human vitreous, and identified differences between embryonic and young adult vitreous proteomes[ 21 ]. In this study, we identified only 466 proteins, 299 of these are new and have not been previously reported in either of aforementioned studies excluding that by Murphy et al[ 20 ] ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%